Biodiesel production and evaluation of heterogeneous catalyst using South African oil producing trees - Modiba, Edward Magoma (Vaal University of Technology, 2014)
This study presents the use of sodium methoxide as a homogeneous catalyst and impregnated Perlite (potassium hydroxide/perlite) as heterogeneous catalyst for production of biodiesel using Baobab and Marula oil respectively. One factor at a time experimental design was used to study the effect of temperature, time, amount of catalyst and methanol to oil ratio on the transesterification of baobab oil using sodium methoxide as a catalyst. Response surface methodology was used to study the effect of temperature, time, amount of catalyst and methanol to oil ratio on the transesterification of marula oil using perlite as a catalyst. Biodiesel yield produced using sodium methoxide and baobab oil was 96% at 1 hr reaction time, 30 wt.% methanol to oil ratio, 1 gram of catalyst and 60°C reaction conditions. Biodiesel yield produced using perlite and marula oil was 91.38% at 3.55 hr reaction time, 29.86 wt.% methanol to oil ratio, 3.46 grams of catalyst and 70.41°C reaction conditions. Perlite catalyst was reusable for transesterification of marula oil while sodium methoxide was not reusable for transesterification of baobab oil. Baobab and Marula biodiesel fuel properties are comparable to American Society for Testing Materials standard (ASTM).
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Biodiesel production; Evaluation of heterogeneous catalyst; Baobab and Marula Oil; Perlite catalyst; Dissertations, Academic -- South Africa.; Biodiesel fuels.; Heterogeneous catalysis.